Beam based characterization of the European Synchrotron Radiation Facility Extremely Brilliant Source short range wakefield model - L. R. Carver; T. Brochard; E. Buratin; N. Carmignani; F. Ewald; L. Hoummi; S. M. Liuzzo; T. Perron; B. Roche; S. White (Physical Review Accelerators and Beams, 2023)
The European Synchrotron Radiation Facility (ESRF) storage ring (SR) has been dismantled and replaced by the Extremely Brilliant Source (EBS) which has now been commissioned. This new fourth generation light source has much smaller vacuum chambers than its predecessor, which necessitates a careful optimization of the vacuum systems and an accurate impedance model to be able to deliver all beam modes at the design current and predict future machine performance in the presence of strong collective effects. This paper will report on the first beam based measurements with a single bunch in order to characterize the short range wakefield model of the EBS SR and to make a first comparison with predictions. The results from transverse instability thresholds and tune shift measurements will be presented, as well as bunch length and phase variation with the current. Microwave instability threshold measurements have shown some discrepancy with predictions, which could arise from welding defects in the machining of the chambers. These discrepancies and other possible causes will be discussed.